The Immune‐Related Gene CD48 Is a Prognostic Biomarker Associated With the Breast Cancer Tumor Microenvironment - Yi Zhao; Hengheng Zhang; Wenwen Wang; Guoshuang Shen; Miaozhou Wang; Zhen Liu; Jiuda Zhao; Jinming Li (iLabmed)
ABSTRACT Background While tumor cells can affect the biological behavior of malignant tumors, the tumor microenvironment (TME) also plays an important role in the occurrence, development, and metastasis of tumors. The dynamic changes in the immune and stromal components of the TME and their correlations with breast cancer (BCa) patient prognosis may help guide clinical practice. Methods In this study, transcriptomic data and clinical information of BCa samples were obtained from The Cancer Genome Atlas database. The immune score and matrix score were calculated using the ESTIMATE algorithm. Examining the differentially expressed genes (DEGs), protein–protein interaction network development, and univariate Cox analysis helped identify CD48 as a key BCa‐related gene. Results The DEG and survival analysis results showed that CD48 was significantly upregulated in BCa samples compared with normal samples, potentially affecting patient prognosis. Gene set enrichment analysis showed that high CD48 expression was mainly associated with immune‐related pathways, suggesting that CD48 may be an important factor for maintaining an immune‐dominant TME in BCa. Analysis of tumor‐infiltrating immune cell types showed that high expression of CD48 could inhibit the infiltration of M2 macrophages and promote the entry of CD8+ T cells, CD4+ T cells, and M1 macrophages into the TME to exert anti‐tumor effects. Conclusions CD48 may serve as an effective biomarker for predicting BCa patient prognosis and a potential immune‐related therapeutic target.